Relationships between lower-body muscle structure and, lower-body strength, explosiveness and eccentric leg stiffness in adolescent athletes - Secomb, J. L.; Nimphius, S.; Farley, O. R L.; Lundgren, L. E.; Tran, T. T.; Sheppard, J. M. (Journal of Sports Science & Medicine, 2015)
The purpose of the present study was to determine whether any relationships were present between lower-body muscle structure and, lower-body strength, variables measured during a countermovement jump (CMJ) and squat jump (SJ), and eccentric leg stiffness, in adolescent athletes. Thirty junior male (n = 23) and female (n = 7) surfing athletes (14.8 ± 1.7 y; 1.63 ± 0.09 m; 54.8 ± 12.1 kg) undertook lower-body muscle structure assessment with ultrasonography and performed a; CMJ, SJ and an isometric mid-thigh pull (IMTP). In addition, eccentric leg stiffness was calculated from variables of the CMJ and IMTP. Moderate to very large relationships (r = 0.46-0.73) were identified between the thickness of the vastus lateralis (VL) and lateral gastrocnemius (LG) muscles, and VL pennation angle and; peak force (PF) in the CMJ, SJ and IMTP. Additionally, moderate to large relationships (r = 0.37-0.59) were found between eccentric leg stiffness and; VL and LG thickness, VL pennation angle, and LG fascicle length, with a large relationship (r = 0.59) also present with IMTP PF. These results suggest that greater thickness of the VL and LG were related to improved maximal dynamic and isometric strength, likely due to increased hypertrophy of the extensor muscles. Furthermore, this increased thickness was related to greater eccentric leg stiffness, as the associated enhanced lower-body strength likely allowed for greater neuromuscular activation, and hence less compliance, during a stretch-shortening cycle.